History and progress in genetic improvement for enhancing rice yield in sub-Saharan Africa - Futakuchi, K.; Senthilkumar, Kalimuthu; Arouna, A.; Vandamme, Elke; Diagne, M.; Zhao, D.; Manneh, B.; Saito, Kazuki (Elsevier, 2021)
Genetic improvement has been given high priority in rice research for development in sub-Saharan Africa (SSA). This paper provides an overview of historical efforts of genetic improvement in SSA focused on improving rice productivity. It further describes yield gain of new rice varieties evaluated in recent field experiments in four selected breeding target domains, and summarizes adoption studies on rice varieties. Efforts to develop rice varieties adapted to diverse rice production systems in SSA have been made by several research organizations, including national agricultural research institutes, bilateral organizations, and three CGIAR centers. The efforts have resulted in the release of around 570 rice varieties in 10 major rice-producing SSA countries by 2020. Among these varieties, the most well-known are interspecfic upland rice varieties “New Rice for Africa (NERICA)” that were developed from crosses between improved Oryza sativa tropical japonica and Oryza glaberrima varieties. However, recent field assessements demonstrated that upland rice yield can be further improved through introduction of upland indica materials from Asia. In contrast, lowland interspecific rice varieties out-yielded the previously released improved O. sativa varieties in selected SSA countries. Field assessments in Senegal and Madagascar did not demonstrate the yield advantage of the recently-developed varieties including hybrids over best performing ones released before. The adoption level of improved varieties in terms of share of area occupied by improved varieties in 18 SSA countries was 40 % in 2008 with old varieties that were released before 2000 being dominant and 7% of the total rice area occupied by NERICA varieties. Especially in irrigated and rainfed lowland rice systems, the majority of dominant varieties were still those introduced from Asia. Panel data between 2002 and 2019 from the Senegal River Valley also confirmed this, and Sahel 108, which was introduced from Asia and released in Senegal in 1994, accounted for >70 % of the total rice area in both the wet and dry seasons in 2019. The implications of this review for future rice genetic improvement and varietal replacement in SSA are discussed.